Investigating Possibility of Predicting Turnover of Indian it Engineers Based on Quality of Work Life Using ANN - Sarabjit Kaur, Dr.Shivinder Nijjer, Dr. Jaskirat Singh Tanveer Kajla, Tanuj Sharma (International Journal of Advanced Science and Technology, 2019)
The Indian IT sector witnesses a high annual turnover rate, with the increase in average annual attrition rate by 1% at the industry level for the year 2018. The figures also suggest that attrition is highest among medium and senior-level professionals, in tier 2 cities, especially in new technology areas. Although the firms have put in massive efforts like upskilling, reskilling, offering massive retention bonuses and offering client-facing roles, the attrition is still daunting many firms. Therefore, it is imperative to discern the root cause of attrition and it is plausible to view the same from multiple perspectives – considering both internal and external factors. One such prominent factor affecting turnover intention is Quality of work life, which has been analysed in this work. The focus of the work is to predict how the quality of work-life of middle-level engineers in Indian IT firms, affects and aids in predicting their turnover intention. The tool of analysis is Artificial Neural Networks. Keywords: Quality of Work Life, Turnover, IT Engineers, Indian IT industry, Prediction, ANN